1995
DOI: 10.1152/ajpendo.1995.269.2.e290
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-stimulated regulation of blood-follicle barrier is mediated by nitric oxide

Abstract: Although initially described over 30 years ago, the blood-follicle barrier has remained a biological enigma. In this study, we characterize the blood-follicle barrier with respect to its regulation of intrafollicular inter-alpha-trypsin inhibitor protein (I alpha I) influx after an ovulatory stimulus. We have found that I alpha I is localized within the ovarian vasculature but is excluded from the follicular compartment until an ovulatory stimulus is given. Within minutes after an ovulatory dose of human chori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 20 publications
5
63
1
Order By: Relevance
“…During cumulus expansion, the blood-follicle barrier opens and allows the influx of members of the ITI family, as well as the enzymatic factor required to form the SHAP-HA complex when the cumulus cells initiate extensive HA synthesis (21,22). A granulosa cell-derived factor with similar enzyme activity has also been reported (23).…”
Section: Absence Of the Shap-ha Complex Caused The Defect Of The Ha-rmentioning
confidence: 99%
“…During cumulus expansion, the blood-follicle barrier opens and allows the influx of members of the ITI family, as well as the enzymatic factor required to form the SHAP-HA complex when the cumulus cells initiate extensive HA synthesis (21,22). A granulosa cell-derived factor with similar enzyme activity has also been reported (23).…”
Section: Absence Of the Shap-ha Complex Caused The Defect Of The Ha-rmentioning
confidence: 99%
“…Bikunin attaches to heavy chains 1, 2, or 3 (also known as serum-derived hyaluronan-associated proteins or SHAPs) via its chondroitin sulphate side chain. In some species, serum-derived inter-␣-trypsin inhibitor crosses the follicular basal lamina after the LH surge (Powers et al, 1995) and becomes covalently crosslinked to hyaluronan, releasing free bikunin in the process and stabilizing the expanding cumulus matrix (Chen et al, 1996;Hess et al, 1999). Thus, cumulus expansion when performed in vitro requires the presence of serum or inter-␣-trypsin inhibitor to retain hyalunonan in a stable complex.…”
Section: Extracellular Matrix Of the Oocyte And Cumulus Cellsmentioning
confidence: 99%
“…It has been reported that iNOS or eNOS could be detected in porcine or mouse follicles, granulosa cells, cumulus cells and oocytes (Hattori et al 2001, Takesue et al 2003, Mitchell et al 2004. Expression of eNOS increases after the luteinizing hormone surge or human chorionic gonadotropin (hCG) injection (Van Voorhis et al 1995, Jablonka-Shariff & Olson 1998, Nakamura et al 1999, and eNOS-derived NO stimulates the ovulatory process (Shukovski & Tsafriri 1994, Powers et al 1995, Bonello et al 1996, Hesla et al 1997, Yamauchi et al 1997, Jablonka-Shariff & Olson 1998, Jablonka-Shariff et al 1999. The reports about changes in iNOS expression during this process are controversial (Matsumi et al 1998), and the role of iNOS-derived NO is unclear.…”
Section: Introductionmentioning
confidence: 99%